Work-family interaction: perceptions concerning balance and role demand - Aziz, Azelin; Chang, Artemis (2014)
Women’s participation in paid employment has become a common scenario even in non-Western developing countries.Nevertheless, with the differences in the cultural and contextual factors across nations, variations in the work-family experiences are expected.This study was carried out to explore how non-Western Malaysian people perceive the meaning of a balanced work-family life, as well as to identify the types of role demands surfacing in their work and family roles – employing Malaysia women teachers as the study sample. This study identified some unique findings relating to this matter, suggesting the influence of cultural and the contextual factors in the work-family interrelationship.